A burden of sarcomere gene variants in fetal-onset patients with left ventricular noncompaction. (1st April 2021) - Hirono, Keiichi; Hata, Yukiko; Ozawa, Sayaka Watanabe; Toda, Takako; Momoi, Nobuo; Fukuda, Yutaka; Inuzuka, Ryo; Nagamine, Hiroki; Sakaguchi, Heima; Kurosaki, Kenichi; Okabe, Mako; Takarada, Shinya; et al.
Abstract: Background: Left ventricular noncompaction (LVNC) is a hereditary cardiomyopathy, associated with high morbidity and mortality, but the role of genetics in cases of fetal-onset has not been fully evaluated. The goal of this study was to identify the genetic background in LVNC fetal-onset patients using next-generation sequencing (NGS). Methods: Thirty-three fetal-onset Japanese probands with LVNC (20 males and 13 females) were enrolled. In the enrolled patients, 81 genes associated with cardiomyopathy were screened using next-generation sequencing (NGS) retrospectively. Results: Twenty-three patients had congestive heart failure (CHF), and six patients had arrhythmias. Prominent trabeculations were mostly observed in lateral LV, posterior LV, and apex of LV in patients with LVNC. Twelve died; three patients experienced intrauterine death or termination of pregnancy. Overall, 15 variants were found among eight genes in 16 patients. Seven variants were detected in MYH7 and two in TPM1. Sarcomere gene variants accounted for 75.0%. A multivariable proportional hazards model revealed that CHF at diagnosis and a higher ratio of the noncompacted layer/compacted layer in the LV posterior wall were independent risk factors for death in LVNC fetal-onset patients (odds ratio = 4.26 × 10 6 and 1.36 × 10 8, p = 0.0075 and 0.0005, respectively). Conclusions: The present study is the first report focusing on genetic background combined with clinical features in LVNC fetal-onset patients using NGS. Sarcomere variants were most commonly identified in fetal-onset patients, and greater attention should be paid to fetal-onset patients with LVNC having prominent trabeculations in the LV because they are more likely to develop CHF. Highlights: The first report focusing on genetic background in LVNC fetal-onset patients. Sarcomere variants were most commonly identified. Higher noncompacted to compacted ratio of left ventricle was risk factors for death.